Three-Dimensional Computed Tomographic Study of the Supratrochlear Artery and Supraorbital Artery to Determine Arterial Variations and Their Relationship. Issue 2 (16th February 2022) - Liao, Zhi-Feng; Cong, Li-Yao; Hong, Wei-Jin; Luo, Cheng-En; Luo, Sheng-Kang
Abstract : BACKGROUND: The forehead has high risks associated with filler injection considering its highly complex vascular system. This study aims to thoroughly describe the anatomical variations and relationships between the supratrochlear artery (STA) and supraorbital artery (SOA). MATERIALS AND METHODS: We studied 56 cadaveric heads by computed tomography after contrast-agent injection. RESULTS: The deep branch of the STA originated in the deep superior orbital arcade and the ophthalmic artery (OA), whereas that of the SOA originated at 3 locations: the deep superior orbital arcade, deep superior orbital artery, and OA. The superficial branch of the STA also had 3 origins: the superficial superior orbital arcade, OA, and angular artery, whereas the superficial branch of the SOA had 2 origins: the superficial superior orbital arcade and OA. Based on the relationship between the STA and SOA, 2 main arterial distribution patterns were observed in both superficial and deep layer arteries: STA/SOA connected pattern and STA/SOA disconnected pattern, of which the latter pattern has 3 subtypes. CONCLUSION: The forehead arteries have complex origins. The relationship of the supratrochlear and supraorbital arteries could be categorized into 2 main patterns. The study elucidated the complexity of the forehead vasculature.